Experimental Validation of Critical Heat Flux (CHF) Predictive Methods for a New Synthetic fluid with Low Environmental Impact. (December 2015) - Botticella, Francesco; Imparato, Walter; Viscito, Luca
Abstract: This work presents experimental critical heat flux (CHF) values for a low environmental impact synthetic refrigerant and their comparison with well-known correlations from scientific literature. Tests were performed with HFO-1234yf in an aluminum heat sink made up of seven mini-channels, each of them 2 mm wide and 1 mm high. The heated length was 25 mm. Experiments have been obtained in a variety of thermodynamic condition: the R1234yf saturation temperatures T sat ranged from 25 up to 65 °C (corresponding to medium-to-high reduced pressures), whilst the mass fluxes G had been fixed to 150 up to 300 kg/m 2 s. The tests have been carried out by increasing the heat dissipated by the boiling refrigerant until the thermal crisis occurred and the corresponding heat flux value was recorded as CHF. The experimental results were finally compared to the well-known correlations of Wojtan et al.[1], Kuan[2], Katto-Ohno[3], Zhang et al.[4] and Anwar et al.[5] to investigate their effectiveness with the present data. The latter correlation was found to better predict the experimental values.